Responses of mature symbiotic nodules to the whole-plant systemic nitrogen signaling. (9th May 2020) - Lambert, Ilana; Pervent, Marjorie; Le Queré, Antoine; Clément, Gilles; Tauzin, Marc; Severac, Dany; Benezech, Claire; Tillard, Pascal; Martin-Magniette, Marie-Laure; Colella, Stefano; Lepetit, Marc
Abstract : The effect of systemic signaling of whole-plant N demand on mature N2 -fixing nodules was investigated. Sugar allocation and hormones are candidates to integrate symbiotic nodules to whole-plant nutritional demand. Abstract: In symbiotic root nodules of legumes, terminally differentiated rhizobia fix atmospheric N2 producing an NH4 + influx that is assimilated by the plant. The plant, in return, provides photosynthates that fuel the symbiotic nitrogen acquisition. Mechanisms responsible for the adjustment of the symbiotic capacity to the plant N demand remain poorly understood. We have investigated the role of systemic signaling of whole-plant N demand on the mature N2 -fixing nodules of the model symbiotic association Medicago truncatula / Sinorhizobium using split-root systems. The whole-plant N-satiety signaling rapidly triggers reductions of both N2 fixation and allocation of sugars to the nodule. These responses are associated with the induction of nodule senescence and the activation of plant defenses against microbes, as well as variations in sugars transport and nodule metabolism. The whole-plant N-deficit responses mirror these changes: a rapid increase of sucrose allocation in response to N-deficit is associated with a stimulation of nodule functioning and development resulting in nodule expansion in the long term. Physiological, transcriptomic, and metabolomic data together provide evidence for strong integration of symbiotic nodules into whole-plant nitrogen demand by systemic signaling and suggest roles for sugar allocation and hormones in the signaling mechanisms.